2018
DOI: 10.1093/ecco-jcc/jjy109
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes With Therapeutic Drug Monitoring in Inflammatory Bowel Disease: A Systematic Review With Meta-Analysis

Abstract: The existing limited evidence does not support an association between any TDM strategy and superior clinical remission rates but does support a cost savings benefit [particularly for reactive TDM] and suggests a potential benefit for anti-TNF durability [particularly proactive TDM]. Additional, longer-term studies are needed, particularly to further investigate proactive TDM, and to generate data on other anti-TNF agents, the induction period and paediatric populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
53
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 31 publications
1
53
1
7
Order By: Relevance
“…Many IBD experts believe that proactive‐TDM leads to timely escalation of therapy, higher clinical remission rates, reduced immunogenicity (the development of clinically significant antibodies to IFX), cost reduction and a reduction in the loss of response to IFX . A recently published systematic review on the clinical outcomes of therapeutic drug monitoring in IBD included nine studies and found that there was not sufficient evidence to support one method of therapeutic drug monitoring (Reactive vs Proactive) over the other, in particular relating to clinical remission rates but did recognise that there was a potential for cost reduction with reactive therapeutic drug monitoring (reactive‐TDM) . As a consequence, the present guidelines advise that there is a lack of sufficient evidence to introduce the routine use of proactive‐TDM in the treatment of IBD patients.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many IBD experts believe that proactive‐TDM leads to timely escalation of therapy, higher clinical remission rates, reduced immunogenicity (the development of clinically significant antibodies to IFX), cost reduction and a reduction in the loss of response to IFX . A recently published systematic review on the clinical outcomes of therapeutic drug monitoring in IBD included nine studies and found that there was not sufficient evidence to support one method of therapeutic drug monitoring (Reactive vs Proactive) over the other, in particular relating to clinical remission rates but did recognise that there was a potential for cost reduction with reactive therapeutic drug monitoring (reactive‐TDM) . As a consequence, the present guidelines advise that there is a lack of sufficient evidence to introduce the routine use of proactive‐TDM in the treatment of IBD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The AGA advised that based on the research available at the time of the guideline, there was insufficient evidence to support the routine use of proactive‐TDM; however, the guideline failed to mention a number of important factors when reviewing the effectiveness of proactive‐TDM. A major omission in the guideline published by the AGA was the exclusion of the development of anti‐drug antibodies to IFX as an endpoint and a second major endpoint that was missing from the guideline was the discontinuation of IFX therapy . The European Crohn's and Colitis Organisation's guidelines on the management of ulcerative colitis (UC) acknowledge that therapeutic drug monitoring is being increasingly adopted to try to optimise outcomes, particularly during maintenance treatment but does not conclude with a specific recommendation for therapeutic drug monitoring …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Higher serum biological drug concentrations, lower fecal calprotectin levels, and a tight disease control approach are associated with favorable therapeutic outcomes in CD. 4,5 However, the best strategy for CD monitoring and its implications on treatment decisions has yet to be defined. The CALM Q5 trial conducted by Colombel et al 5 showed…”
mentioning
confidence: 99%